Canada and the U.S.: What Makes Us Different? A Response to Seymour Martin Lipset - Conway, J. F. (Labour / Le Travail, 1991)
The article reviews several books by Seymour Martin Lipset including "Continental Divide: The Values and Institutions of the United States and Canada," "North American Cultures: Values and Institutions in Canada and the United States," and "Unions in Transition: Entering the Second Century."
Keywords: BOOKS -- Reviews; CONTINENTAL Divide: The Values & Institutions of the United States & Canada (Book); LIPSET, Seymour Martin, 1922-2006; NORTH American Cultures: Values & Institutions in Canada & the United States (Book); Nonfiction; UNIONS in Transition: Entering the Second Century (Book)